MASSIVE LEIOMYOSARCOMA OF THE MAXILLA - Riaz, Nabeela; Warriach, Riaz Ahmad; Aftab, Asma (Journal of Ayub Medical College Abbottabad, 2011)
Leiomyosarcoma is a malignant smooth-muscle tumour that is exceedingly rare in the head and neck region. Presenting signs and symptoms of leiomyosarcoma in the orofacial region are generally nonspecific. The tumour is commonly encountered as a slow growing, discreet firm, and non-ulcerated painless mass. We presented a case of massive leiomyosarcoma of the midface which might be the first leiomyosarcoma of midface reported in Pakistan so far to our knowledge. We also discuss the diagnosis and treatment of leiomyosarcoma in this aspect. Keyword: Leiomyosarcoma, tumour, malignant, orofacial